IMPLEMENTATION OF STUNTING REDUCTION POLICY IN MUARA JAWA DISTRICT, KUTAI KARTANEGARA REGENCY - Abdul Mufid; Kus Indarto; Cathas Teguh Prakoso; Bambang Irawan; Enos Paselle; Saipul (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to implement the Policy to Reduce Stunting Rates in Muara Jawa Subdistrict, Kutai Kartanegara Regency, and to examine the supporting and inhibiting factors that influence its implementation. This study uses a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The Implementation Framework refers to Edward III's theory, which covers four dimensions of policy implementation: communication, resources, disposition, and bureaucratic structure, adding two additional dimensions, namely supporting and inhibiting factors.The results of the study show that the implementation of the policy to reduce stunting rates in Muara Jawa Subdistrict is driven by a very strong and integrated governance system, supported by factors of communication (very effective and consistent), disposition (high and controlled commitment), and bureaucratic structure (adaptive and convergent). The main strength lies in the authoritative authority of the sub-district head, who has successfully controlled sectoral egos and integrated financial resources quickly through the involvement of the village head (TPPS). However, the overall effectiveness of implementation is structurally hampered by a serious resource deficit. These obstacles include a quantitative deficit of technical human resources (nutritionists/midwives) and volunteers (cadres) who are vulnerable due to high workloads and low incentives, as well as a structural deficit of sensitive intervention facilities (sanitation and clean water) that require large budgets beyond the authority of the sub-district level. Strengthening structural resources, enhancing functional human resource support, and enriching educational communication.